A Spy in the House of Art: The Marxist Criticism of Anthony Blunt. Issue 2 (3rd April 2018) - Bounds, Philip
Abstract : Anthony Blunt's writings on the visual arts have not received as much scholarly attention as they deserve, not least because Blunt's reputation was seriously tarnished by the revelation that he had worked as a Soviet spy. This article examines the writings on art which Blunt produced under the influence of Marxism in the 1930s. Among its central concerns is Blunt's attitude towards the Soviet ideas about culture which did so much to shape British communist criticism between the wars. It is argued that Blunt's response to Soviet aesthetic orthodoxy was a curiously ambivalent one. On the one hand, Blunt went far beyond any other British writer in welcoming the Soviet belief that artists should take their instructions from the socialist state. On the other hand, while posing as an apologist for the Soviet doctrine of Socialist Realism, he was clearly unimpressed by existing examples of socialist art and seemed suspicious of the way in which Socialist Realism had been theorised by Soviet critics. His lukewarm response to Socialist Realism was expressed directly in his writings on contemporary painters and more obliquely in his historical work on the visual culture of the Renaissance. By the same token, in spite of trotting out formulaic condemnations of surrealism, abstraction and other modernist forms, Blunt was unhappy with the Soviet prohibition on modernism and found it difficult to conceal his belief that painters had much to learn from modern art. In the final analysis, Blunt's ambivalence towards Soviet theory gives his work a highly representative quality. Like many other British Marxist critics of his time, Blunt took Soviet ideas as his starting point but often developed them in unexpected and sometimes unorthodox ways. His work serves as a valuable reminder that British communist criticism between the wars was never merely a pale reflection of Soviet orthodoxy.